1973
DOI: 10.1177/001440297304000108
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Bias in the Diagnosis of Mental Retardation

Abstract: Rosenthal, R. Unintended effects of the clinician in clinical interaction: A taxonomy and a review of clinician expect ancy effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Early research indicated that social class bias is present (Abramowitz & Dokecki, 1977). That is, mental illness was more often reported when a client's background was described as being lower‐class rather than middle‐class or upper‐class and when the clinicians were given Rorschach Inkblot Test results (Haase, 1964; Trachtman, 1971), case history information and IQ scores (Neer, Foster, Jones, & Reynolds, 1973), or recordings of an interview (DiNardo, 1975; Lee & Temerlin, 1970). The effect of social class was also significant in a later study when clinicians made diagnoses after viewing videotapes of interviews (Luepnitz, Randolph, & Gutsch, 1982).…”
Section: Social Class Biasmentioning
confidence: 99%
“…Early research indicated that social class bias is present (Abramowitz & Dokecki, 1977). That is, mental illness was more often reported when a client's background was described as being lower‐class rather than middle‐class or upper‐class and when the clinicians were given Rorschach Inkblot Test results (Haase, 1964; Trachtman, 1971), case history information and IQ scores (Neer, Foster, Jones, & Reynolds, 1973), or recordings of an interview (DiNardo, 1975; Lee & Temerlin, 1970). The effect of social class was also significant in a later study when clinicians made diagnoses after viewing videotapes of interviews (Luepnitz, Randolph, & Gutsch, 1982).…”
Section: Social Class Biasmentioning
confidence: 99%
“…Different results have been reported among classroom teachers. One early study (Neer, Foster, Jones, & Reynolds, 1973) showed a greater tendency among teachers to diagnose mild mental retardation (MMH) in low SES children. Similarly, Giesbrecht and Routh (1979) reported that teachers were more likely to recommend SE services for low SES blacks than high SES blacks.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…For example, it has been demonstrated that teachers hold different attitudes toward children as a function of the children's sex (Jackson & Lahaderne, 1967;Palardy, 1969), race (Rubovits & Maehr, 1973), socioeconomic status (SES) (Bergan & Smith, 1966;Lenkowsky & Blackman, 1968;Neer, Foster, Jones, & Reynolds, 1973), physical appearance (Berscheid & Walster, 1974;Dion, 1972), name (Staffieri, 1976), perceived intelligence (Matuszek & Oakland, 1979;Rubovits & Maehr, 1971), and behavior (Algozzine, Mercer, & Countermine, 1977;Giesbrecht & Routh, 1979;LaVoie & Adams, 1974).…”
mentioning
confidence: 99%